Assessment of brown adipose tissue function - Virtue, Samuel; Vidal-Puig, Antonio (Frontiers in Physiology, 2013)
In this review we discuss practical considerations for the assessment of brown adipose tissue in rodent models, focusing on mice. The central aim of the review is to provide a critical appraisal of the utility of specialised techniques for assessing brown adipose tissue function in vivo. We cover several of the most common specialised methods for analysing brown adipose tissue function in vivo, including assessment of maximal thermogenic capacity by indirect calorimetry and the measurement of sympathetic tone to brown adipose tissue. While these techniques are powerful, they are not readily available to all laboratories; therefore we also cover several simple measurements that, particularly in combination, can be used to determine if a mouse model is likely to have alterations in brown adipose tissue function. Such techniques include: pair feeding, analysis of brown adipose tissue lipid content and mRNA and protein markers of brown adipose tissue activation.